أثر أزمة انهيار أسعار المحروقات على صناديق الثروة السيادية - دراسة قياسية في الفترة ما بين سبتمبر 2007 و ديسمبر2015- - مجاني, غنية; قريسي, ياسين (جامعة الوادي - University of Eloued, 2017)
تستحوذ أصول صناديق الثروة السيادية النفطية على 56.6% من إجمالي أصول صناديق الثروة السيادية، و يعتبر سعر النفط متغير معنوي و هام جدا في تحديدها. لقد تأثر سعر النفط في الثلاثي الرابع من سنة 2014 بمجموعة من المتغيرات الاقتصادية و السياسة كزيادة العرض من دول خارج OPEC، تباطؤ نمو الطلب العالمي ، استغلال الغاز الصخري و ارتفاع مخزون النفط ، تراجع مؤشرات اقتصادية في الصين و ارتفاع سعر صرف الدولار، كما ساهم الوضع السياسي المتأزم في مناطق الإنتاج في انهيار أسعار النفط ، ولدراسة أثر أسعار المحروقات على هذه الصناديق السيادية تم تقدير نموذج VAR و الاستعانة بتقنية دوال الاستجابة ، حيث استنتجنا أن هنالك أثر ايجابي لصدمة أسعار النفط على أصول صناديق الثروة السيادية. During the last years , the assets of oil sovereign wealth funds have known growth thanks to rising oil prices, but from 2014, the price of oil has seen a big decline because of many economic and political factors such as : the increase in the supply of non-OPEC countries, the decline in international demand for hydrocarbons, the exploitation of shale gas, the increase in oil stocks, the decline in China's economic indexes, and the valuation of the exchange rate of the dollar. Moreover, the geopolitical crisis in the production areas played an important role in the fall in oil prices. In order to measure the impact of oil prices on sovereign wealth funds assets, we opted for the use of the Auto-RegressiveVector Model (VAR), where we deduced the positive effect of oil prices on the assets of the sovereign wealth funds.
The impact of the collapse of fuel prices on sovereign wealth funds - A standard study between September 2007 and December 2015-
مقال
Keywords: أصول صناديق الثروة السيادية، أزمة انهيار أسعار البترول، نموذج; VAR. sovereignwealthfunds, oilcrisis, Auto-Regressive Vector Model (VAR).